Association of Retinal Layer Thickness With Cognition in Patients With Multiple Sclerosis. Issue 4 (July 2021) - Baetge, Sharon Jean; Dietrich, Michael; Filser, Melanie; Renner, Alina; Stute, Nathalie; Gasis, Marcia; Weise, Margit; Lepka, Klaudia; Graf, Jonas; Goebels, Norbert; Hartung, Hans-Peter; Aktas, Orhan; et al.
Abstract : Objective: Retinal layer thickness (RLT) measured by optical coherence tomography (OCT) is considered a noninvasive, cost-efficient marker of neurodegeneration in multiple sclerosis (MS). We aimed to investigate associations of RLT with cognitive performance and its potential as indicator of cognitive status in patients with MS by performing generalized estimating equation (GEE) analyses. Methods: In this cross-sectional study, patients with at least mild signs of cognitive impairment were examined by OCT as well as by the Brief International Cognitive Assessment for MS and tests assessing attention and executive functions (Trail Making Test [TMT] A and B). Associations of these factors were investigated using GEE models controlling for demographic and disease-related factors and correcting for multiple testing. Results: A total of 64 patients entered the study. In the final sample (n = 50 [n = 14 excluded due to missing data or drop-outs]; n = 44 relapsing-remitting MS and n = 6 secondary progressive MS, mean Expanded Disability Status Scale score = 2.59 [SD = 1.17], disease duration [median] = 7.34 [interquartile range = 12.1]), 36.0% were cognitively impaired. RLT of the macular retinal nerve fiber layer was associated with performance in TMT-B (β = −0.259). Analyses focusing on the upper and lower tertile of RLT additionally revealed associations between macular ganglion cell-inner plexiform layer and TMT-B and verbal short-term memory and learning, respectively. Conclusion: In patients with MS, at less advanced disease stages, RLT was especially associated with cognitive flexibility promoting OCT as a potential marker advocating further extensive neuropsychological examination.